Correlation of Radiological Severity of Genu Osteoarthritis (Kellgren and Lawrence) with Functional Disabilities (Womac Score) - Novita, Mitha; Nyimas Fatimah (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Background: Osteoarthritis (OA) is a degenerative disease that most often causes functional disabilities. Thecomplaints that most often cause functional disabilities in people with OA are pain and stiffness. The severity of OAcan be seen radiologically. The aim of this study was to assess the correlation of radiological severity of OA (Kellgrenand Lawrence) with functional disabilities (WOMAC score). Method: This type of research is an analytic observationalstudy with a cross sectional design. The population who became the respondents of this study were patients sufferingfrom knee osteoarthritis at the Medical Rehabilitation Installation of Dr. Mohammad Hoesin Hospital, Palembang inNovember 2018 who met the inclusion criteria. Samples were taken by consecutive sampling technique. Thefunctional ability of the patient will be assessed using the WOMAC score and the severity of OA radiologicallyinterpreted based on the Kellgren and Lawrence criteria. Result: Statistical test used Somer's correlation test. From 32respondents' data, it was found that there was no significant correlation between the radiological severity of OA andfunctional disability (p = 0.097). Conclusion: There is no significant correlation between radiological severity of OA(Kellgren and Lawrence) with functional disabilities (WOMAC score).